2020
DOI: 10.3892/ol.2020.11428
|View full text |Cite
|
Sign up to set email alerts
|

RRM2 elicits the metastatic potential of breast cancer cells by regulating cell invasion, migration and VEGF expression via the PI3K/AKT signaling

Abstract: Breast cancer is the second leading primary cause for cancer-related mortality among women and metastasis to the brain is a disastrous event for patients with increasing incidence. A previous study confirmed the critical function of RRM2 in breast cancer cell growth. Unfortunately, the role and fundamental molecular mechanism of RRM2 in breast cancer metastasis remains elusive. In the current study, higher RRM2 expression was validated in breast cancer tissues, especially in the brain metastasis group. Simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Deregulated expression, prognostic value as well as therapeutic exploitation of RRM2 has been reported in various types of cancer over the past decade including prostate cancer [11,12], glioblastoma [13], colorectal cancer [14], melanoma [15], Ewing sarcoma [10], cervical [16] and breast cancer [17,18]. Besides the finding of RRM2 as part of a four-gene prognostic signature in high-risk neuroblastoma and a recent report with limited data showing that siRNA mediated knockdown in SH-SY5Y cells caused a cell cycle arrest concomitant with apoptosis induction [19], the functional role of RRM2 in neuroblastoma tumorigenesis has remained unexplored thus far.…”
Section: Functional In Vitro and In Vivo Validation Of Rrm2 As A Novementioning
confidence: 99%
“…Deregulated expression, prognostic value as well as therapeutic exploitation of RRM2 has been reported in various types of cancer over the past decade including prostate cancer [11,12], glioblastoma [13], colorectal cancer [14], melanoma [15], Ewing sarcoma [10], cervical [16] and breast cancer [17,18]. Besides the finding of RRM2 as part of a four-gene prognostic signature in high-risk neuroblastoma and a recent report with limited data showing that siRNA mediated knockdown in SH-SY5Y cells caused a cell cycle arrest concomitant with apoptosis induction [19], the functional role of RRM2 in neuroblastoma tumorigenesis has remained unexplored thus far.…”
Section: Functional In Vitro and In Vivo Validation Of Rrm2 As A Novementioning
confidence: 99%
“…Putluri et al observed that inhibiting RRM2 in BC cells significantly decreased proliferation and the expression of cell cycle genes and sensitized cells to tamoxifen treatment [65]. In agreement with the potential relevance of RRM2, additional studies have reported a reduction in proliferation [85,126] and tamoxifen resistance [158] in BC cell lines following RRM2 inhibition. Furthermore, associations between RRM2 overexpression and deterioration in BC survival have been widely reported, strongly suggesting a role as a targeted therapy for BC [61,120,121].…”
Section: Multi-omics Studies and Novel Bc Treatment Strategiesmentioning
confidence: 81%
“…The authors observed a significant correlation between poor survival of BC patients and changes to the expression of RRM2 and adenosine monophosphate deaminase 1 (AMPD1), a key enzyme in de novo purine synthesis. These enzymes have been postulated as promising therapeutic targets in different tumor types, including BC [65,85,[123][124][125][126].…”
Section: Multi-omics Studies Of Bc Prognosismentioning
confidence: 99%
“…However, RRM2 is closely associated with sensitivity to Adriamycin. Inhibition of pancreatic cancer cell lines by co-administration of Adriamycin and RRM2 siRNA was four times higher than that provided by Adriamycin administration alone ( 41 ).RRM2 overexpression upregulates VEGF in oral and pancreatic cancers and promotes tumor angiogenesis through the PI3K/AKT signaling pathway ( 42 , 43 ). Certain TKIs may benefit patients with liposarcoma.…”
Section: Discussionmentioning
confidence: 99%